A self-assembled multi-enzyme nanomachine and whole-cell biocatalyst for the sustainable valorization of marine biomass into fermentable sugars and consolidated bioprocessing - Lee, Myeong-Eun; Bhardwaj, Nisha; Cho, Byeong-Hyeon; Hyeon, Jeong Eun; Jeong, Wu-Young; Han, Sung Ok (International journal of biological macromolecules, 2025)
Marine biomass is a potential resource that contains functional carbohydrates, such as agar, carrageenan, and cellulose, and can be modified for various applications. A novel self-assembled multi-enzyme nanomachine (SAMN) and its whole-cell biocatalyst were developed to target the degradation of marine biomass components and enable consolidated bioprocessing. Compared to each representative single enzyme, the marine biomass-degrading SAMN exhibited an average 1.45-fold higher hydrolytic activity for six of the seven substrates. The modification of SAMN with MglB further enhanced the hydrolytic activities toward agar, agarose, lambda-carrageenan, and agar-carrageenans-cellulose mixed substrate. Moreover, SAMN displayed a maximum thermostability increase of 14.10%. The SAMN and the SAMN with MglB produced a maximum of 2.25 ± 0.04 mM and 2.33 ± 0.03 mM galactose, a functional sugar from real red algae, respectively. The Saccharomyces cerevisiae-based whole-cell biocatalyst displaying SAMN with MglB produced 2.00 ± 0.14 g/L ethanol from real red algae as the sole carbon source, achieving the highest production among all samples. This marine biomass-degrading SAMN and its whole-cell biocatalyst have potential applications in the saccharification and consolidated bioprocessing of marine biomass, leading to the production of functional sugars and value-added bio-based products in industrial settings. [Display omitted] •Self-assembled multi-enzyme nanomachine (SAMN) was newly developed.•SAMN showed enhanced hydrolysis activity toward marine biomass-related substrates.•SAMN was thermostable in the condition of high temperature.•The modified SAMN produced maximum 2.33 ± 0.03 mM galactose from real red algae.•The SAMN-displaying whole-cell biocatalyst produced 2.00 ± 0.14 g/L ethanol from real red algae.